RoMEO studies 7: creation of a controlled vocabulary to analyse copyright transfer agreements - Jenkins, Celia; Oppenheim, Charles; Probets, Steve; Hubbard, Bill (Sage Publications, 2008)
This paper describes the process of creating a controlled vocabulary which can be used to systematically analyse the copyright transfer agreements (CTAs) of journal publishers with regard to self-archiving. The analysis formed the basis of the newly created Copyright Knowledge Bank of publishers’ self-archiving policies. Self-archiving terms appearing in publishers’ CTAs were identified and classified, with these then being simplified, merged, and discarded to form a definitive list. The controlled vocabulary consists of three categories that describe ‘what’ can be self-archived, the ‘conditions’ of self-archiving and the ‘restrictions’ of self-archiving. Condition terms include specifications such as ‘where’ an article can be self archived, restriction terms include specifications such as ‘when’ the article can be self archived. Additional information on any of these terms appears in ‘free-text’ fields. Although this controlled vocabulary provides an effective way of analysing CTAs, it will need to be continually reviewed and updated in light of any major new additions to the terms used in publishers’ copyright and self-archiving policies.